Human protein-based porous scaffolds as platforms for xeno-free 3D cell culture - Santos, Sara C. (2022)
Extracellular matrix and protein-based biomaterials emerge as attractive sources to produce scaffolds due to their great properties regarding biocompatibility and bioactivity. In addition, there are concerns regarding the use of animal-derived supplements in cell culture not only due to the risk of transmission of xenogeneic contaminants and antigens but also due to ethical issues associated with collection methods. Herein, a novel human protein-derived porous scaffold produced from platelet lysates (PL) as platform for xeno-free 3D cell culture has been proposed. Human PL are chemically modified with methacryloyl groups (PLMA) to make them photocrosslinkable and used as precursor material to produce PLMA-based sponges. The herein reported human-based sponges have highly tunable morphology and mechanical properties, with an internal porous structure and Young's modulus dependent on the concentration of the polymer. Human adipose-derived stem cells (hASCs) are cultured on top of PLMA sponges to validate their use for 3D cell culture in xeno-free conditions. After 14 days hASCs remained viable, and results show that cells are able to proliferate during time even in the absence of animal-derived supplementation. This study reveals for the first time that such scaffolds can be promising platforms for culture of human cells avoiding the use of any animal-derived supplement.